Molecular Mechanisms of Trastuzumab-Based Treatment in HER2-Overexpressing Breast Cancer. (22nd November 2012) - Nahta, Rita
Abstract : The past decade of research into HER2-overexpressing breast cancer has provided significant insight into the mechanisms by which HER2 signaling drives tumor progression, as well as potential mechanisms by which cancer cells escape the anticancer activity of HER2-targeted therapy. Many of these preclinical findings have been translated into clinical development, resulting in novel combinations of HER2-targeted therapies and combinations of trastuzumab plus inhibitors of resistance pathways. In this paper, we will discuss proposed mechanisms of trastuzumab resistance, including epitope masking, cross signaling from other cell surface receptors, hyperactive downstream signaling, and failure to induce antibody-dependent cellular cytotoxicity. In addition, we will discuss the molecular mechanisms of action of dual HER2 inhibition, specifically the combination of trastuzumab plus lapatinib or trastuzumab with pertuzumab. We will also discuss data supporting therapeutic combinations of trastuzumab with agents targeted against molecules implicated in trastuzumab resistance. The roles of insulin-like growth factor-I receptor and the estrogen receptor are discussed in the context of resistance to HER2-targeted therapies. Finally, we will examine the major issues that need to be addressed in order to translate these combinations from the bench to the clinic, including the need to establish relevant biomarkers to select for those patients who are most likely to benefit from a particular drug combination.